National and International Civilian Protection Strategies in the Israeli-Palestinian Conflict - Spitka, Timea (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"In this book, Timea Spitka raises hopeful possibilities to transform the Israel-Palestinian conflict. She considers the many national and international governmental and nongovernmental organizations, which recognize global norms to protect an ethno-religious group from state genocide or subjugation. Significantly, she assesses their actions, which have made varying contributions to protect the Palestinians in the territories subjected to Israeli military control. This research unravels some of the myths and contradictions in traditional national and security studies and focuses on the delivery and gaps in the protection of civilians." - Louis Kriesberg, Professor Emeritus of Social Conflict Studies, Syracuse University, US. This open access book examines security and protection within Israel and Palestine, analyzing national and international security strategies that apply to the protection of civilians. The author examines the principles, practices and the perception of protection. Focusing on protection strategies and practices in the Israeli-Palestinian conflict, this book reveals some of the myths and enigmas of national and international protection of civilians. The book moves beyond the current lack of protection strategies to discuss more effective human security focused on prioritizing protection of civilians, use of alternative tools such as community policing and inclusive protection. Timea Spitka is a current fellow at the Norman Patterson School of International Affairs, Carleton University in Ottawa, Canada. She was previously a post-doctoral fellow and a researcher at Hebrew University, Israel, and a researcher in Security Studies at the Masaryk University, Czech Republic. Timea has worked for international organizations including the United Nations and Oxfam in several conflict zones including Bosnia and Herzegovina and Israel/Palestine. Her main areas of research and expertise are on human security, global responsibility to protect, gender and children's rights. She is the author of several articles including: Normative Canadian Foreign Policy Towards Consensus on the IsraeliPalestinian Conflict and the author of the book: International Intervention, Identity and Conflict Transformation: Bridges and Walls Between Groups.